2023
DOI: 10.3389/pore.2022.1610808
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of long non-coding RNA MALAT1 in hepatocellular carcinoma: A study based on multi-omics analysis and RT-PCR validation

Abstract: Background: This study aimed to explore the relationship between MALAT1 and the prognosis of patients with hepatocellular carcinoma (HCC).Methods: We constructed a MALAT1 protein-protein interaction network using the STRING database and a network of competing endogenous RNAs (ceRNAs) using the StarBase database. Using data from the GEPIA2 database, we studied the association between genes in these networks and survival of patients with HCC. The potential mechanisms underlying the relationship between MALAT1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…Furthermore, LINC00161 expression was positively correlated with serum AFP concentration and the TNM stage [ 81 ], indicating that exosomal lncRNAs could reflect additional clinical characteristics. Liao et al [ 82 ] analyzed the relationship between exosomal MALAT1 and the prognosis of HCC. The results show that the high expression of exosomal MALAT1 was significantly related to shorter progression-free survival and shorter overall survival, which exhibited moderate predictive power (AUC range from 0.661 to 0.731).…”
Section: Exosome Cargos As Biomarkers For Hccmentioning
confidence: 99%
“…Furthermore, LINC00161 expression was positively correlated with serum AFP concentration and the TNM stage [ 81 ], indicating that exosomal lncRNAs could reflect additional clinical characteristics. Liao et al [ 82 ] analyzed the relationship between exosomal MALAT1 and the prognosis of HCC. The results show that the high expression of exosomal MALAT1 was significantly related to shorter progression-free survival and shorter overall survival, which exhibited moderate predictive power (AUC range from 0.661 to 0.731).…”
Section: Exosome Cargos As Biomarkers For Hccmentioning
confidence: 99%
“…Importantly, as a key lncRNA that involved in HCC progression, MALAT1 (metastasis-associated lung adenocarcinoma transcript 1) can affect cell proliferation, apoptosis, and migration ( Lu et al, 2021 ). It has been verified that MALAT1 is overexpressed in HCC and is associated with shorter overall survival, serving as a prognostic marker for patients with HCC ( Liao et al, 2022 ). However, whether MALAT1 interacts with ferroptosis-related signaling pathways to regulate HCC biological function is needed to be further investigated.…”
Section: Ferroptosis-related Ncrnas In Hccmentioning
confidence: 99%
“…Furthermore, the role of the RNA m 6 A modification in many biological processes and diseases has been elucidated in the past decade; these processes include autophagy, cell proliferation, stem-cell renewal and differentiation, and the diseases include tumorigenesis, and cardiovascular diseases [139,146,148,149]. In the past three years, several studies have shown that RNA m 6 A marks are involved in the regulation of ferroptosis and thus affects the progression of diseases such as tumor growth and acute kidney injury [133,150,151] and that m 6 A modification regulators used in combination with ferroptosis-related genes can be diagnostic or prognostic markers for tumors in humans [130,[152][153][154][155]. Multiple m 6 A modification regulators have been shown to be aberrantly expressed in various types of tumors, and a prediction model comprising these regulators and ferroptosis-associated genes has been shown to effectively reflect the progression and prognosis of these tumor patients [23,[156][157][158][159].…”
Section: The Rna M 6 a Modification In Ferroptosismentioning
confidence: 99%
“…Generally, hypermethylation in the promoter or transcriptional start site or hypomethylation in the coding sequence of a gene suppresses the expression of that gene. However, it should be noted that the expression of a methylated gene can be increased when either the coding sequence is hypermethylated or the promoter or transcriptional start site is hypomethylated 130 . Thus, DNA methylation in coding regions needs to be further studied, especially when no difference in overall DNA methylation is identified, and the distribution of DNA methylation throughout the genome needs to characterized.…”
Section: Dna Methylation In Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation